Babylonien und Israel: Historische, religiöse und sprachliche Beziehungen (1991)
Sammlung von früheren Aufsätzen u.a. von H. Donner, W.G. Lambert, W. von Soden, M. Weippert, B. Landsberger, H.-?. Müller